(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
One of retrofit material is a material made from epoxy resin. This material is generally mixed with epoxy resin, hardener, and filler so that it can be applied to concrete surfaces. This research used fly ash and sand as filler for epoxy resin and hardener. A Good filler can be impacted to high mechanical strength due to molecules density as filler. This research is directed to find out the results slump flow, setting time, compressive strength, and flexural strength to be produced with a mixture of epoxy as much as 15%-30% and type F fly ash as much as 5%-20%. The results showed that the setting time for the fastest initial time and final time are 85 minutes and 125 minutes. This result is faster than normal mortar with 90 minutes of initial time and 1440 minutes of final time. The longest initial time and final time are 125 minutes and 165 minutes. Minimum initial time and final time is obtained from 5% of fly ash and 30% of epoxy. The compressive strength result of 28 days with variation 20% of fly ash and 15% epoxy from its mixtures obtained the maximum compressive strength 97,71 MPa and minimum variation mixture is obtained as 87,71 MPa with 5% fly ash and 30% epoxy. The flexural strength result of 28 days with variation 20% of fly as and 15% epoxy is obtained the maximum flexural value 46,60 MPa and the value of minimum variation mixture as 39,31MPa is obtained from 5% of fly ash and 30% of epoxy.